Անվանի հայերը Ղաջարական Իրանում - Թաջարյան, Իվեթ (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The significance of the Qajar dynasty in the modern history of Iran has been widely studied in historiography. The assessment of that dynasty has not always been unequivocal. It was characterized as a flourishing period on the one hand, and a period of decline on the other. During the Qajar Dynasty, the Iranian Armenians made immense contribution towards the development of Iran’s economy and arts. They were also able to make obvious advancements in the social and political life of the country receiving high-ranking positions.
Keywords: Պատմություն